The Impact of Vertical Integration on Physician Behavior and Healthcare Delivery: Evidence from Gastroenterology Practices - Saghafian, Soroush; Song, Lina; Newhouse, Joseph; Landrum, Mary Beth; Hsu, John (Management Science, 2023)
The U.S. healthcare system is undergoing a period of substantial change with hospitals purchasing many physician practices (“vertical integration”). In theory, this vertical integration could improve quality by promoting care coordination but could also worsen it by impacting the care delivery patterns. The evidence quantifying these effects is limited because of the lack of understanding of how physicians’ behaviors alter in response to the changes in financial ownership and incentive structures of the integrated organizations. We study the impact of vertical integration by examining Medicare patients treated by gastroenterologists, a specialty with a large outpatient volume and a recent increase in vertical integration. Using a causal model and large-scale patient-level national panel data that includes 2.6 million patient visits across 5,488 physicians, we examine changes in various measures of care delivery. We find that physicians significantly alter their care process (e.g., in using anesthesia with deep sedation) after they vertically integrate, and there is a substantial increase in patients’ postprocedure complications. We further provide evidence that the financial incentive structure of the integrated practices is the main reason for the changes in physician behavior because it discourages the integrated practices from allocating expensive resources to relatively unprofitable procedures. We also find that, although integration improves operational efficiency (e.g., measured by physicians’ throughput), it negatively affects quality and overall spending. Finally, to shed light on potential mechanisms through which policymakers can mitigate the negative consequences of vertical integration, we perform both mediation and cost-effectiveness analyses and highlight some useful policy levers. This paper was accepted by Stefan Scholtes, healthcare management. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2023.4886 .